Towards Automated Meta-Analysis of Biomedical Texts in the Field of Cell-Based Immunotherapy - Devyatkin, D.A.; Molodchenkov, A.I.; Lukin, A.V.; Kim, Y.S.; Boyko, A.A.; Karalkin, P.A.; Chiang, J.-H.; Volkova, G.D.; Lupatov, A.Yu. (Biomedical Chemistry: Research and Methods, 2019)
Cell-based immunotherapy is a promising approach for the treatment of chronic infections, autoimmune disorders, and malignant tumors. There are many strategies of cell-based immunotherapy of cancer; these include injection of various immune effector cells, propagated and «trained» in a cell culture. Alternatively, cells presenting tumor antigens on their surface in a form recognized by the immune system can be used to achieve a therapeutic effect. The research results in this field are presented in thousands of texts, and their manual analysis is very complicated. We have developed an approach for automated text analysis in this area of biomedical science. Here we present the first results of the automated analysis of the data extracted from abstracts of scientific articles available in PubMed. These results demonstrate the associations between types of tumors and the most commonly used methods of their cell-based immunotherapy.